An outcome evaluation of the psychotherapeutic milieu therapy programme of the William Slater Centre for adolescents and young adults. - Ahmed, Nazeema (Department of Psychology, 2024)
Adolescence is a significant developmental period during which individuals experience serious mental health problems. Research over the past two decades has demonstrated high morbidity, and at times, mortality for this age group. Adolescent depression has received much attention, since a significant proportion of adolescents have been found to suffer from depressive disorders or clinical levels of depressive symptomatology. This has led mental health professionals to develop effective intervention programmes for the youth. At present, numerous forms of therapeutic interventions exist for adolescents and young adults. A result of the increasing numbers of psychotherapeutic programmes for adolescents was a need to determine its efficacy. Programme evaluation methods have been increasingly utilised to evaluate the functioning and outcome of treatment programmes. It was this approach which informed the present study. The aim of this thesis was to conduct an outcome evaluation of the William Slater Centre for Adolescents and Young Adults' psychotherapeutic milieu treatment programme. This thesis arises from the drawbacks of a previous thesis which examined the structure, process and shortterm outcome of the William Slater Centre's programme. The present thesis aims to obtain a profile and an indication of the functioning of a group of adolescents who were discharged from the William Slater Centre's 12-week therapeutic programme. A combination of quantitative and qualitative methods were used. The study is a limited, retrospective analysis of the existing records of the William Slater Centre. Post-discharge questionnaires were distributed to adolescent patients who had completed the 12-week therapeutic programme at intervals of 6 month, 18 month and 36 month post-discharge. The questionnaire was designed to determine the long-term efficacy of the Centre's psychotherapeutic programme. It includes a Beck Depression Inventory, a Youth SelfReport Scale and a General Health Questionnaire. Due to the small sample sizes of adolescents who returned the questionnaires at the three time periods, a sample of 83 adolescents who completed the 6 and 18 month post-discharge questionnaire formed the basis of the present study. The sample of 93 adolescents not responding to the questionnaires were also analysed. The analyses resulted in a discussion of the profile of adolescents who returned the questionnaires as well as a description of the adolescents who did not return any of the post-discharge questionnaires. The scores of the Beck Depression Inventory are also analysed. The final part of the thesis provides a qualitative analysis of the comments of adolescents who completed the questionnaires. Results of the study found that adolescents discharged from the Centre's programme comprise a psychiatric population who have histories of psychological difficulties and who appear to be prone to further long standing problems. Qualitative analysis revealed adolescents need for ongoing psychiatric or psychological assistance. Quantitative analysis of the depression rating scales demonstrate that the majority of adolescents improved significantly since their initial assessment to the Centre. These findings are supported by the large number of adolescents reporting on their positive experiences of the Centre's therapeutic programme. The thesis demonstrates that strong outcomes are difficult to predict with a sample of depressed adolescents.